The Impact of Delivery, Menu Variety, Pricing, Promotion, and Food Quality on Customer Satisfaction: Mediated by Perceived Value - Azura Abdullah Effendi; Gan Kia Hui; Intan Azmira Binti Che Kahar; Irdina Humaira Binti Mohamad Sukeri; Irene Lee Xiang Ming; Jasmine Wong Jia Xuan; Jayaneswari A/P Vartharaju; Griselda Joan N; Anees Janee Ali; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Foodpanda struggles with delayed deliveries, inconsistent food quality, limited menu variety, and pricing issues, leading to ongoing customer dissatisfaction despite promotional efforts. This study examines the impact of delivery experience, menu variety, pricing perception, promotion, and food quality on customer satisfaction with Foodpanda Malaysia, with customer perceived value as a mediator. A total of 135 respondents were surveyed to investigate how these factors influence customer satisfaction. The results show that Foodpanda's customer satisfaction is driven by delivery experience, pricing perception, food quality, and customer perceived value, with pricing perception being the most influential. Menu variety and promotion type have no significant impact. Delivery experience and pricing perception also indirectly boost satisfaction by enhancing perceived value, whereas menu variety, promotion type, and food quality do not significantly affect perceived value. The study highlights the importance of perceived value as a mediator, offering actionable insights for improving customer experience in the food delivery industry.